Cancer risk awareness and screening uptake in individuals at higher risk for colon cancer: a cross-sectional study. Issue 12 (20th December 2016) - Salimzadeh, Hamideh; Bishehsari, Faraz; Delavari, Alireza; Barzin, Gilda; Amani, Mohammad; Majidi, Azam; Sadjadi, Alireza; Malekzadeh, Reza
Abstract : Objective: We aimed to measure cancer knowledge and feasibility of a screening colonoscopy among a cohort of individuals at higher risk of colon cancer. Methods: This study was conducted as part of an ongoing screening cohort, in which first degree relatives (FDRs) of patients with colon cancer are invited to participate in a free of charge screening colonoscopy. We enrolled 1017 FDRs in the study between 2013 and 2014 measuring their data on demographics, cancer knowledge and colonoscopy uptake. A p value of <0.05 was considered statistically significant. Results: The relative's mean age was 48.7 years. Only about 28% of FDRs were aware of their increased risk for cancer, near 35.0% had ever heard about colonoscopy with 22% aware of the correct age to start screening. Comparing cancer knowledge of FDRs at high risk versus those at moderate risk, we recorded non-significant differences (p>0.05). Almost two-thirds of FDRs expressed willingness to undergo a colonoscopy and 49.2% completed the procedure, of which 12.8% had advanced neoplasm. Conclusions: Our data indicated that remarkable numbers of FDRs were not still informed of their cancer risk or never received a physician recommendation for screening. The desirable uptake at first invitation, which would be higher over successive invitations, supports the feasibility of a family-based recruitment approach for early screening. This has promising implications to introduce targeted screening colonoscopy into the healthcare system in Iran and other developing nations.